2005
DOI: 10.1086/491736
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatocyte Fas Expression and Apoptosis in HIV and Hepatitis C Virus Coinfection

Abstract: HCV/HIV-coinfected patients show higher levels of hepatocytes expressing Fas and undergoing irreversible apoptosis than do HCV-infected patients. However, low CD4+ cell nadirs in coinfected patients are associated with hepatocyte Fas expression and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…While the exact mechanisms for advanced fibrosis in co-infection are not entirely clear, several studies have shed light on this interaction. Both HIV and HCV infection can induce hepatocyte apoptosis via activation of the TRAIL receptors, and increase TRAIL expression by hepatocytes 32,80. HIV infection renders hepatocytes sensitive to TRAIL with increased TRAIL-R2 expression.…”
Section: Co-infection With Viral Hepatitismentioning
confidence: 99%
“…While the exact mechanisms for advanced fibrosis in co-infection are not entirely clear, several studies have shed light on this interaction. Both HIV and HCV infection can induce hepatocyte apoptosis via activation of the TRAIL receptors, and increase TRAIL expression by hepatocytes 32,80. HIV infection renders hepatocytes sensitive to TRAIL with increased TRAIL-R2 expression.…”
Section: Co-infection With Viral Hepatitismentioning
confidence: 99%
“…Tuyama et al [38 ] recently were able to demonstrate the possibility of HIV to directly infect hepatic stellate cells and induce enhanced collagen production in an in-vitro model. Immunostaining of liver biopsies demonstrated that HIV might enhance hepatocyte apoptosis [39] and proliferation [40], which could add to the higher risk for fibrosis progression in HIV/HCV-coinfected individuals. Interesting data on intrahepatic mRNA levels of cytokines and cellular markers that compares liver biopsies of HCV/HIV-coinfected patients with HCVmonoinfected ones was recently published [41].…”
Section: Molecular Pathologymentioning
confidence: 99%
“…17,18 There is also an increase in steatohepatitis, which in turn up-regulates inflammation in the liver and is pro-fibrogenic. 19,20 Finally, there is also evidence that HIV directly infects the stellate cells, and this promotes inflammation and secretion of fibrogenic stroma.…”
Section: Pathogenesismentioning
confidence: 99%